Dielectric relaxations in starch-water solutions. (20th July 2015) - Yadem, Clement; Repo, Tapani; Silvennoinen, Raimo
Abstract: We demonstrate the effect of water-soluble starch on an electrochemical impedance spectrum with the aim of sensing starch concentration in an aqueous solution. The characteristic form of the relative dielectric dispersion curves with respective loss factors was shown to relate to the severity of the starch concentration at a frequency range from 200 Hz up to 500 kHz. It was also remarkable to recognize that even in a lower frequency regime, for instance from 0.1 Hz up to 200 Hz, the spectral peaks in the dispersion curves of the dielectric loss factors were observable with separate consecutive relaxation times. According to the results of this study, this clearly demonstrates the reliability of these features when estimating the concentration of starch in aqueous starch solutions.